The Effectiveness of Digital Da'wah Media: A Case Study of Assajidin.Com and the Transformation of Religious Understanding in Palembang - D. Rosadi, Nora Juwita; Bukhori, K.A.; Nasution, Nurseri Hasnah; Bin Abdullah, Rahmat (Universitas Nurul Jadid, 2025)
In the digital era, online media plays a significant role in spreading Islamic teachings. Assajidin.com is one of the platforms used for da'wah purposes. This study aims to analyse the effectiveness of da'wah through Assajidin.com online media towards the congregation of Al Furqon Palembang study. This research method involves in-depth analysis of the content provided by Assajidin.com. The research approach uses qualitative methods, while the data collection techniques are observation, documentation, and interviews. The results showed that, the effectiveness of Assajidin.com online media is considered good because it fulfils the indicators of media effectiveness, in the form of attractiveness (media attractiveness), media clarity, and media completeness. Assajidin.com content attracts the congregation of Al Furqon Palembang study, and can increase religious understanding. While the ease of access, there are some elderly congregants who are not familiar with the use of online media but are more comfortable with face-to-face studies. Although Assajidin.com offers wide and easy access to useful da'wah material, there are several challenges that affect its effectiveness. Limited access to technology among the congregation, especially the elderly, as well as the lack of skills in using online media are the main obstacles.